Physical, tactical and technical performance of the most demanding passages of kinematic activity in elite soccer - Cortez, A.; Yousefian, F.; Folgado, H.; Brito, J.; Travassos, B.; Abade, E.; Liu, H.; Niu, Z.; Gonçalves, B. (BMC Sports Science, Medicine and Rehabilitation, 2026)
This study examined the changes in physical, tactical, and technical performance during the most demanding passage of kinematic activity (MDPk) and immediately after (post-MDPk) in elite soccer players, with respect to their playing positions. The MDPk (= 15 km/h), was defined using a 1-min rolling average (n = 1016 observations), and was quantified as the distance covered at moderate-speed running (MSR), high-speed running (HSR), and sprinting (SPR). In addition, total distance covered (TD) was also included. Generalized linear mixed models were employed to assess mean changes in five physical, ten tactical, and six technical performance-related variables during the effective playing time from the onset of the MDPk to 1-min post-MDPk, across different playing positions. Across all positions, there was a significant decrease in all external load variables during the 1-min post-MDPk period (TD=-48%; MDPk=-89%; MSR=-84%; HSR=-93%; SPR=-97%). All technical variables exhibited a substantial decline in the post-MDPk regardless of playing positions, particularly in passes for wide midfielders and central forwards, and shots by central forwards. Team tactical variables decreased in the post-MDPk, especially for ball-in-play percentage and number of possession changes. Central defenders, fullbacks and central midfielders spent more time in their own third in the post period and running more towards their own goal in the MDPk, whereas WM and CF spent more time in opponent`s third in the post period.